Photochemical reactions of biomass derived platform chemicals - Hoffmann, Norbert; Gomez Fernandez, Mario Andrés; Desvals, Arthur; Lefebvre, Corentin; Michelin, Clément; Latrache, Mohammed (Frontiers in Chemistry, 2024)
Platform chemicals obtained from biomass will play an important role in chemical industry. Already existing compounds or not yet established chemicals are produced from this renewable feedstock. Using photochemical reactions as sustainable method for the conversion of matter furthermore permits to develop ecological and economical interesting processes. Furans or levoglucosenone are thus obtained from carbohydrate containing biomass. Photochemical rearrangements, photooxygenation reaction or photocatalytic radical reactions can be carried out with such compounds. Also, sugars such pentoses or hexoses can be more easily transformed into heterocyclic target compounds when such photochemical reactions are used. Lignin is an important source for aromatic compounds such as vanillin. Photocycloaddition with alkenes or the use light supported multicomponent reactions yield interesting target molecules. Dyes, surfactants or compounds possessing a high degree of molecular diversity and complexity have been synthesized with photochemical key steps. Alkenes as platform chemicals are also produced by fermentation processes, for example with cyanobacteria. Such alkenes as well as terpenes may further be transformed in photochemical reactions yielding, for example, precursors of jet fuels.